Lysosomes of Cancerous and Normal cells in Response to Low-energy/low-dose Medical Diagnostic X-rays - Tungjai, Montree; Tubthaing, Nuttakan; Kothan, Suchart (Bangladesh Journal of Medical Science, 2019)
Background: Low-energy/low-dose ionizing radiation is increasingly being used in medical diagnosis, yet the effects of low-energy/low-dose medical diagnostic X-rays on biological systems remains a mystery. Thus, the aim of this present study is to determine the characteristics of lysosomes of cancerous and normal cells in response to low-energy/low-dose medical diagnostic X-rays. Methods and materials: Three cell lines composed of peripheral blood mononuclear cells (PBMCs), adriamycin-sensitive erythroleukemia cells (K562), and adriamycin-resistant erythroleukemia cells (K562/adr), were all exposed to low-energy/low-dose medical diagnostic X-rays that operated at 50, 70, and 100 kV, and 100 mAs for obtaining radiation doses at 0.03, 0.07, and 0.10 mGy, respectively. Accumulation of acridine orange in the lysosomes of each cell line was determined using flow cytometry completed at 4 and 6 hours-post irradiation. Results: The data showed an increase in fluorescence intensity of acridine orange in three irradiated cells line at 4 hours post-irradiation, but this intensity did not change at 6 hours post-irradiation when compared to that of corresponding non-irradiated cells. Conclusion: This finding suggests that changes in lysosomes might be a response to low-energy/low-dose medical diagnostic X-rays. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.830-834